Cálculo de vulnerabilidad por exposición asociada a las zonas de riesgo y amenaza de inundación del caño(río) Maizaro en el municipio de Villavicencio-Colombia. (2020)
The following research Project focused on the Maizaro river located in the urban area of Villavicencio city, capital of the Meta department. It aimed at calculating and analyzing the vulnerability of the area due to the exposure to different affecting components such as ecosystems, infrastructure, population, and production systems. The study above was accomplished with information obtained from the cartography offered by national institutes such as IGAC or IDEAM. Then, it was processed using geographic information system in order to complete de proposed methodology and condense the results of the analysis of vulnerability in a raster model associated with the zoning of areas with threat and risk conditions by flooding of Maizaro river.